Impact of statin use on cancer recurrence and mortality in breast cancer: A systematic review and meta‐analysis. Issue 6 (31st May 2016) - Manthravadi, Sashidhar; Shrestha, Anuj; Madhusudhana, Sheshadri
Abstract : Statins have shown antineoplastic properties in preclinical studies with breast cancer cells. They inhibit the enzyme "HMG CoA reductase" and the expression of this enzyme in cancer cells has been implicated as a favorable prognostic factor in patients with breast cancer. After a search of MEDLINE and Embase from inception through November 2015, 817 abstracts were reviewed to identify studies that described an association between statin use and outcomes in breast cancer. A total of 14 studies which included 75, 684 women were identified. In a meta‐analysis of 10 studies, statin use was associated with improved recurrence‐free survival (RFS; HR 0.64; 95% CI 0.53–0.79, I 2  = 44%). Furthermore, this RFS benefit appeared to be confined to use of lipophilic statins (HR 0.72; 95% CI 0.59–0.89) as hydrophilic statin use was not associated with improvement in RFS (HR 0.80; 95% CI 0.44–1.46). Statin users similarly showed improved overall survival in a meta‐analysis with substantial heterogeneity (8 studies, HR 0.66; 95% CI 0.44–0.99, I 2  = 89%). Statin users also had improved cancer‐specific survival, although this relationship was measured with less precision (six studies, HR 0.70; 95% CI 0.46–1.06, I 2  = 86%). In conclusion, breast cancer patients who use statins, or specifically, lipophilic statins show improved recurrence‐free survival. Statin users also had improved overall survival and cancer‐specific survival. These findings should be assessed in a prospective randomized cohort and the choice of statin, dose and biomarkers that may predict the efficacy of these drugs should be identified. Abstract : What's new? Mounting evidence suggests that statins can protect against breast cancer recurrence, while preclinical studies have revealed that the cholesterol‐lowering drugs possess antineoplastic activity against breast cancer cells. This meta‐analysis of observational studies further reinforces the idea that statins possess chemopreventive and antineoplastic activities. Of 14 studies included in the analysis, 10 reported a link between statin use and improved recurrence‐free survival in patients with breast cancer. Other studies revealed an association with improved all‐cause mortality in breast cancer patients. The findings raise the need for validation in a prospective randomized clinical trial.